Love's rescue [large type] : a novel - Johnson, Christine (Christine Elizabeth) (Center Point Large Print, 2015)
"When her mother dies, Elizabeth Benjamin heads home to Key West, determined to transform herself into the perfect Southern belle her parents always wished her to be. But nothing goes according to plan. As family secrets come to light, Elizabeth is faced with a difficult choice: to do her duty or follow her dreams"--